Study of the Outcome of Mental Strength Development Program in Adolescents by the Resilient Development Program for Teenagers - Ruetathip, Naruepak; Rujirachakon, Satreerat (Medical Journal of Sakon Nakhon Hospital, 2024)
The resilience is a tool to promote, support and develop adolescents to be mentally strong, have self–esteem and a sense of self–worth, adaptable when experience the disappointment or psychological impact. This is important for teenagers in growing up and step into a qualified adult. This study aimed to evaluate the outcome of the mental strength development program in adolescents by using the resilient development program for teenagers. This is an experimental research with unequal control and case groups in students of Sanom Wittayakarn School, Surin province conducted in 3 days. The 69 samples were selected by using a simple random sampling. The samples were divided into 2 groups, the experimental group consisted of 40 students and control group consisted of 29 students. The research instrument consisted of the resilience questionnaire scale RS–48, 13–18 years developed by the department of Mental Health. Data were analyzed by using the percentage, mean, standard deviation, and t–test. The results showed that most of the samples were female, aged 13–15 years. After receiving the mental strength development program in adolescents by using the resilient development program for adolescents, the experimental group had significantly higher resilience than that before implementing the program (p < 0.05).